If we build it, who will benefit? A multi-criteria approach for the prioritization of new bicycle lanes in Quebec City, Canada - Emily Grisé; Ahmed El-Geneidy (Journal of Transport and Land Use)
Many cities across the world are actively promoting cycling through investments in cycling infrastructure, yet ensuring that the benefits from these investments are distributed equally in a region and not benefiting only one group is an important social goal. The aim of this study is to develop a methodology that can help in identifying where new bicycle facilities can be built in a region while prioritizing investments for those who need them most. The study uses Quebec City, Canada, as an example since the city has recently made a strong commitment to provide safe and attractive bicycle infrastructure to its residents. It also uses a GIS-based grid cell model to identify priority areas for cycling investment in different parts of the city. This is followed by a proposal for a new set of facilities based on a multi-criteria approach. These proposed facilities are then evaluated through a level of usage analysis to determine which routes will provide the maximum benefit to existing and potential cyclists. Finally, an equity analysis is conducted to evaluate whether the new facilities will meet some of the travel needs of individuals residing in socially deprived neighborhoods. This step in the evaluation process proposes a new social equity component in bicycle planning processes. This research can be of value to planners, engineers and policymakers working toward investments in bicycle facilities because it shows the full process of planning and evaluating different cycling facilities while incorporating social equity principles.